Effect of black point disease on quality of wheat grain - Malaker, PK; Mian, IH; Bhuiyan, KA; Reza, MMA; Mannan, MA (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted to determine the effect of different levels of black point infection caused by Bipolaris sorokiniana and other fungal pathogens on some quality characters of wheat grain. Wheat grains were graded on a 0-5 scale based on levels of black point infection. Quality characters of grain viz., protein, fat, dry matter, ash and mineral contents under different grades were determined following standard methods. The dry matter and ash contents of grain decreased while the contents of protein and fat increased with the increasing severity of black point infection. The observations on macro and micro nutrient contents of grain indicated that the amount of nitrogen, phosphorus, calcium, magnesium, sulphur, and boron increased, whereas the contents of potassium, iron, zinc, copper and sodium decreased with the increase of black point infection. However, the reductions in copper content of black point affected grains under different grades of infection were not significant as compared to apparently healthy grains. Key Words: Black point; Bipolaris sorokiniana; grain quality; wheat. DOI: 10.3329/bjar.v34i2.5789 Bangladesh J. Agril. Res. 34(2) : 181-187, June 2009